SOFT SKILLS COMPETENCE DEVELOPMENT OF VOCATIONAL TEACHER CANDIDATES - Sudana, I Made; Raharjo, Dwi Winarno; Supraptono, Eko (Jurnal Penelitian Pendidikan, 2015)
Vocational education curriculum 2013 that applied nationally in the academic year 2014/2015 mandated that religious subject added character educational in which contactwith aspects of soft skills. This needs to be addressed by LPTK as producer vocational teacher candidate, so that future graduates are able to fulfill the mandate of the curriculum. Curriculum vocational teacher candidates who applied seems also still focused on providing hard skills competencies, so that graduates do not have adequate soft skills competence. On the other hand in the world of work has been going on trend shift in terms of hard skills to soft skills.Research and development is designed to go through stages and multiyear to produce soft skills development strategy for prospective teachers of vocational school. Development strategy departs from theoretical studies and mapping needs soft skills aspects of relevant research, analysis and LPTK vocational curriculum, soft skills needs and job requirements of future trends, soft skills required by vocational teachers, teaching soft skills already there, done to map the needs and later for further development until the hypothetical model generated Late models. Subjects were LPTK lecturers, teachers of vocational productive industrials. Data were obtained by observation and interviews, review of documents that the results were analyzed with descriptive qualitative and quantitative techniques. There are several aspects of the soft skills required candidates vocational school teachers, among others: (1) self-discipline, (2) responsibility, (3) the spirit of the work, (4) problem solving, (5) collaboration, (6) the ability of communication, (7) personality, (8) social attitudes, (9) critical thinking, (10) creative thinking and innovative, (11) confidence and (12) self-motivation. Soft skills development strategy skills prospective teachers through extra-curricular with gradual pattern through four stages, namely: (1) the development of talent themselves, (2) environmental adaptation, (3) involvement in the organization and (4) development of social life and soul of educational. There needs to be a policy of the leaders of institutions to incorporate soft skills as part of the curriculum and study for the development of the model and test to kwoning the effectiveness of the model.